What my body looks like and what my body can do: A self-perception explanation of excessive exercise in young adults with anorexia and/or bulimia - Ouellet, Marilou; Monthuy-Blanc, Johana; Pauzé, Robert; Rousseau, Michel; Bouchard, Stéphane (Frontiers in Psychology, 2022)
The present study examined the relationships between quantitative and qualitative dimensions of excessive physical exercise with the physical self-perception’s dimensions and allocentric and egocentric perspectives of body image. The eLoriCorps Immersive Body Rating Scale 1.1, the very short form version of the Physical Self-Inventory and the Exercise and Eating Disorder test were used. The study includes 36 anorexic and bulimic patients seeking an external and specialized transdisciplinary program for eating disorders. Pearson’s correlations and multiple regression analyses were performed to examine the relationship between the variables. Results show a different correlational profile of physical self-perceptions depending on the dimension used to define excessive physical exercise. Perceived physical appearance was the key predictor of the qualitative dimension of excessive physical exercise. Findings suggest that excessive physical exercise in eating disorder patients could be explained by the feeling of competence not only related to physical appearance but also through physical abilities.